Evaluation of the Freedom to Learn Policy through the Teaching Campus Program at Medan State University - Farhan Azra Hasibuan; Mitha Alvia Rosha; Nurhalizah; Julia Ivanna (Journal of Community Service For Indonesian Society, 2023)
This article or writing aims to find out how the campus policy is teaching through the independent campus program at Medan State University. As is well known, the teaching campus is one of the public policy products proclaimed by the Directorate of Learning and Student Affairs, Directorate General of Higher Education, Ministry of Education and Culture. This program aims to provide opportunities for students to be able to hone leadership, character and have teaching and learning experiences. This journal writing uses a research method, namely a qualitative descriptive method. In this study, primary data was obtained directly from students through observation and interviews at the research location that was used as the sample, namely at UNIMED Jalan Jl. Williem Iskandar Pasar V Medan Estate, Kec. Percut Sei Tuan, Deli Serdang Regency, North Sumatra 20371. Data collection techniques in this study were library research and field studies. This study concludes that the evaluation criteria have been met, but there are also those that have not been fully achieved. However, most of the results of the research that has been conducted show that the evaluation criteria for each indicator have been met, this indicates that the evolution of the campus teaching program provides good results at least for now.